Clinical Evaluation of Calotropis Gigantea and Balanites Aegyptiaca on Wound Healing in Bovine - Boch, MR; Thorat, MG; Hazare, SW; Mahesarw, SS; Ingole, RS (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The study was conducted to compare the efficacy of Calotropis gigantea leaves extract ointment and Balanites aegyptiaca roots extract ointment in management of wound healing in bovine. The study was undertaken on the clinical cases of wounds presented at Veterinary Clinic, PGIVAS, Akola. A total 12 clinical cases of bovine with lacerated wounds were divided into two groups, comprising of six animals each. Ethanolic extract ointments of C. gigantea and B. aegyptiaca 10% w/w were clinically evaluated for wound healing activity. Clinical observations such as hemorrhages, swelling, colour of wound, exudation, pain, pus formation and irritation were recorded on every alternate day. Wound contraction was measured on 0, 7th, 14th and 21st day. The quality of wound healing was measured on the basis of percent wound contraction. From the observation of clinical study C. gigantea leaf extract ointment showed better wound contraction than B. aegyptiaca roots extract ointment
Keywords: Wound; Bovine; Calotropis gigantea; Balanites aegyptiaca